Credibility and the Cost of Export Subsidies - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 1991)
Recurring balance of payments crises in countries that pursued import substitution have led some of them to establish a variety of export incentives, in particular subsidies, as a way to revive and re-orient their economies. However, exporters are likely to be uncertain of the government's commitment to export promotion because of the years of neglect. This paper analyzes the issue of the credibility of export subsidies and suggests that a government is able to convince exporters of its commitment only at a cost, which reduces the attractiveness of promoting exports by means of subsidies.